Pengaruh Kepemimpinan dan Loyalitas Kerja Terhadap Kinerja Pegawai pada UPTD Puskesmas Hewokloang Kabupaten Sikka - Ludgerus Haryanto Baek; Yustina Olivia da Silva; Nunsio Handrian Meylano (Jurnal Projemen UNIPA, 2025)
This study aims to: (1) describe the employee performance, leadership, and work loyalty; and (2) analyze the influence of leadership and work loyalty on employee performance, both partially and simultaneously. The population in this study consists of 45 employees at the UPTD Hewokloang Public Health Center in Sikka Regency. Due to the limited population, this research used a census or saturated sampling method. Data were collected through questionnaires and analyzed using descriptive and inferential statistical methods, namely multiple linear regression. Hypothesis testing was carried out using the F-test and t-test. Descriptive analysis results indicate that the variables of employee performance, leadership, and work loyalty all fall under the "good" category. The t-test results show that partially, the leadership variable has a positive and significant effect on employee performance. Furthermore, the work loyalty variable also has a positive and significant effect on employee performance. The F-test results show that simultaneously, leadership and work loyalty significantly affect employee performance. The coefficient of determination analysis shows that the two independent variables in this study can explain 31% of the variation in employee performance at the UPTD Hewokloang Public Health Center, Sikka Regency.